The Effect Of Return On Assets (Roa) And Return On Equity (Roe) Towards Changes In Share Prices (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to test and prove the effect of Return On Assets (ROA) and Return On Equity (ROE) on share prices in the pharmaceutical industry listed on the IDX. The population in the study of pharmaceutical companies listed on the IDX in the 2015-2019 period and the sample used were 6 pharmaceutical companies with a purposive sampling technique. The results of this study indicate that partially ROA has no effect on share prices. In addition, ROE also partially has no effect on share prices. And simultaneously ROA and ROE have no effect on share prices in pharmaceutical companies listed on the IDX in the 2015-2019 period.